2017
DOI: 10.1016/j.tjog.2017.08.009
|View full text |Cite
|
Sign up to set email alerts
|

Pathological discrepancy between colposcopic directed cervical biopsy and Loop Electrosurgical-Excision Procedures (LEEPs) in patients with biopsies proven high grade cervical intraepithelial neoplasia

Abstract: The prevalence of patients with CIN1 or less from LEEP specimens who previously had colposcopic biopsies proven CIN2 or 3 was 16.3%. CIN2 from biopsy was the statistically significant risk factor of CIN1 or less in LEEP specimens.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 12 publications
1
10
1
Order By: Relevance
“…However, there was no association between CIN 2 in colposcopic directed biopsy specimens and CIN 1 or less in LEEP specimens. This finding was different from that of most previous studies which have shown CIN 2 in colposcopic directed biopsy specimens was the predicting factor of having CIN 1 or less in LEEP specimens (Giannella et al, 2015;Nam et al, 2015;Zhang et al, 2015;Noothong et al, 2017). Our study found that low grade colposcopic impression was a predicting factor of having CIN 1 or less in LEEP specimens.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…However, there was no association between CIN 2 in colposcopic directed biopsy specimens and CIN 1 or less in LEEP specimens. This finding was different from that of most previous studies which have shown CIN 2 in colposcopic directed biopsy specimens was the predicting factor of having CIN 1 or less in LEEP specimens (Giannella et al, 2015;Nam et al, 2015;Zhang et al, 2015;Noothong et al, 2017). Our study found that low grade colposcopic impression was a predicting factor of having CIN 1 or less in LEEP specimens.…”
Section: Discussioncontrasting
confidence: 99%
“…This study showed 25.4% of CIN 1 or less in LEEP specimens of patients with colposcopic directed biopsy-confirmed CIN 2-3. Previous studies have reported the prevalence of 14-24% of pathological discrepancy (Ryu et al, 2010;Witt et al, 2012;Rodriguez-Manfredi et al, 2013;Giannella et al, 2015;Nam et al, 2015;Zhang et al, 2015;Noothong et al, 2017). The rates of pathological discrepancy varied because of differences in studied population and definition of pathological discrepancy among studies.…”
Section: Discussionmentioning
confidence: 99%
“…We found that an indication of CIN 2 on pre-conization biopsy and an absence of glandular involvement were also independent relative factors. Previous studies found that CIN 2 in colposcopically directed biopsy specimens was a predicting factor for having CIN 1 or less in LEEP specimens ( 11 , 23 , 24 ). However, glandular involvement has not been found to be associated with negative conization in previous studies.…”
Section: Discussionmentioning
confidence: 94%
“…Long recognizes that, according to Massad, 5.9% of HIVpositive women develop a high-grade lesion among 1,639 study candidates, even though progression rates are reported to be lower among young women. [10] A study in Kenya demonstrated the highest prevalence of RA-HPV serotypes among women living with HIV, reporting that 61% of a series with high-grade lesions had serotypes 16 and / or 18. [11]…”
Section: Factors Related To the Patientmentioning
confidence: 99%